Penerapan P5 (Proyek Penguatan Profil Pelajar Pancasila) Di PAUD Hauriyah Halum - Egydia Slavina; Nia Yuliza Putri; Yusi Desia Ananta (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The aim of the Pancasila Profile Development Project is to improve the profile of Pancasila learning which is in line with the Graduate Competency Standards for PAUD children. The implementation of P5 has been implemented at PAUD Hauriyah Halum which has been running for approximately the last 1 year and this activity is applied to students in TK A and TK B classes. The aim of implementing P5 activities at PAUD Hauriyah Halum is to improve and provide knowledge to young children. to maintain the cleanliness of the surrounding environment and improve skills by making handicrafts from recycled waste around their school. The research method in this article uses a qualitative method with a descriptive approach. The data collection method used interview methods and structured observation techniques, where we observed and recorded information provided by the homeroom teachers of Kindergarten A and Kindergarten B. The research findings show that the implementation of the Pancasila Learning Profile Project at PAUD Hauriyah Halum is progressing satisfactorily and is going well.